Evaluation of JKN Financing Policy and Strategic Procurement of Services for the Sustainability and Quality of Care: A Literature Review - Adzroo Atiiqoh Nur Nabiila; Nasywa Athiyah Zahra; Nazhifa Nurul Azizah; Riswandy Wasir; Cahya Arbitera (Universitas Mandala Waluya, 2026)
The National Health Insurance (JKN) programme is a health financing policy designed to achieve universal health coverage by improving access to healthcare services and providing financial protection for the population. It implements a strategic purchasing approach through capitation and INA-CBGs payment mechanisms to promote efficiency and improve the quality of care. This study aims to evaluate JKN financing policies and the implementation of the strategic purchase of healthcare services by conducting a literature review. A literature review was conducted in accordance with PRISMA 2020 guidelines, involving a systematic search across three academic databases. After screening and an eligibility assessment, ten articles met the inclusion criteria. The results reveal that JKN financing has shifted towards a prospective payment system; however, several challenges persist, including discrepancies between tariffs and actual costs, ineffective claims management and limitations in human resources and information system integration. Meanwhile, strengthening information systems, improving human resource competencies and enhancing coordination among stakeholders are recognised as supporting factors. The study concludes that BPJS Kesehatan should periodically adjust INA-CBG tariffs based on case complexity and actual service costs; primary healthcare facilities should strengthen their gatekeeping function through improved capitation incentive design; and hospitals should prioritise diagnostic coding standardisation and internal claims auditing.